2021
DOI: 10.1021/jacs.1c00211
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Merging of Nonfullerene Acceptor π-Extension and Tetrafluorination Strategies Affords Polymer Solar Cells with >16% Efficiency

Abstract: The end-capping group (EG) is the essential electron-withdrawing component of nonfullerene acceptors (NFAs) in bulk heterojunction (BHJ) organic solar cells (OSCs). To systematically probe the impact of two frequent EG functionalization strategies, π-extension and halogenation, in A-DAD-A type NFAs, we synthesized and characterized four such NFAs: BT-BIC, LIC, L4F, and BO-L4F. To assess the relative importance of these strategies, we contrast these NFAs with the baseline acceptors, Y5 and Y6. Up to 16.6% power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
115
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 69 publications
6
115
0
Order By: Relevance
“…As for the (010) π–π stacking peak, it was located at q = 1.73 Å −1 ( d = 3.63 Å) for both PM6:BTP-S7 and PM6:BTP-S8 blends, but at q = 1.74 Å −1 ( d = 3.61 Å) for PM6:BO-4Cl blend and q = 1.75 Å −1 ( d = 3.59 Å) for PM6:BTP-S9 blend. Above distinct features of molecular packing from the acceptors in the blends might also reveal the molecular packing information in the single crystals of relevant NFAs, as demonstrated in previous works 39 , 44 . Comparing with neat acceptor films, only PM6:BTP-S9 blend could maintain the position of π–π stacking peak as that of neat acceptor, after introducing polymer donor PM6, while the other three blends would all be affected.…”
Section: Resultssupporting
confidence: 64%
“…As for the (010) π–π stacking peak, it was located at q = 1.73 Å −1 ( d = 3.63 Å) for both PM6:BTP-S7 and PM6:BTP-S8 blends, but at q = 1.74 Å −1 ( d = 3.61 Å) for PM6:BO-4Cl blend and q = 1.75 Å −1 ( d = 3.59 Å) for PM6:BTP-S9 blend. Above distinct features of molecular packing from the acceptors in the blends might also reveal the molecular packing information in the single crystals of relevant NFAs, as demonstrated in previous works 39 , 44 . Comparing with neat acceptor films, only PM6:BTP-S9 blend could maintain the position of π–π stacking peak as that of neat acceptor, after introducing polymer donor PM6, while the other three blends would all be affected.…”
Section: Resultssupporting
confidence: 64%
“…The maximum absorption coefficient of neat film is 0.87×10 5 for BTCD‐IC and 1.30×10 5 cm −1 for BTCD‐2FIC. The red‐shifted absorption band and higher absorption coefficient of BTCD‐2FIC relative to BTCD‐IC is attributed to the end‐group fluorination effect, [35,36] which is beneficial to obtain higher J sc in the device. According to the equation: E g opt =1240/ λ onset , the optical bandgaps ( E g opt ) of BTCD‐IC and BTCD‐2FIC are calculated to be 1.46 and 1.45 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[ 58 ] By asymmetrically replacing the end group on one side of Y6 with a thiophene‐fused end group, Luo et al reported an asymmetric Y6 analog called BTP‐2F‐ThCl (Figure 5), which balances the V OC and J SC and fine‐tunes the morphology of blends to realize an over 17% PCE (Table 2). [ 59 ] Such successful cases by optimizing end groups to improve photovoltaic performance of Y6 derivatives can be seen in many reports, such as BTP‐ClBr, [ 60 ] BT‐BO‐L4F, [ 61 ] and BTIC‐2Cl‐γCF 3 . [ 62 ]…”
Section: Y6 and Its Derivativesmentioning
confidence: 99%